2021
DOI: 10.1371/journal.pone.0258977
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of a nuclear factor-kappa B-interacting immune gene network in mice cochleae with age-related hearing loss

Abstract: Epidemiological data suggest that inflammation and innate immunity play significant roles in the pathogenesis of age-related hearing loss (ARHL) in humans. In this mouse study, real-time RT-PCR array targeting 84 immune-related genes revealed that the expressions of 40 genes (47.6%) were differentially regulated with greater than a twofold change in 12-month-old cochleae with ARHL relative to young control mice, 33 (39.3%) of which were upregulated. These differentially regulated genes (DEGs) were involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…NF-κB signaling is key in the development of ARHL ( 17 ). Furthermore, UCHL1 is considered a downstream protein of NF-κB signaling ( 37 ) and is involved in numerous human diseases by regulating NF-κB signaling ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NF-κB signaling is key in the development of ARHL ( 17 ). Furthermore, UCHL1 is considered a downstream protein of NF-κB signaling ( 37 ) and is involved in numerous human diseases by regulating NF-κB signaling ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has elucidated that Sp1 mediates cochlear cell apoptosis in hearing loss models ( 15 , 16 ). Furthermore, it has been also reported that NF-κB participates in the pathogenesis of ARHL via interaction with immune-associated genes ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Uraguchi et al. ( 2021 ) analysed 84 immune-related genes expression in the cochlea of 12-month-old mice with ARHL as compared to the young control mice. They found around 40% of immune-related genes were upregulated in the aged cochlea, including PTGS2.…”
Section: Discussionmentioning
confidence: 99%
“… 2012 ; Uraguchi et al. 2021 ) incur the deleterious effects leading to this damage. Yi-qi Cong-ming (YQCM), a famous decoction composed of 8 herbs including Ginseng radix et rhizome ( Panax ginseng C.A.Mey.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported the upregulation of major proin ammatory molecules, IL1B and IL18rap, in the cochleae of C57BL/6J mice older than 6 months of age. Moreover, the bioinformatic analyses indicated that the differentially regulated genes were involved in functional pathways for cytokine-cytokine receptor interaction, chemokine signaling, TNF signaling, and Toll-like receptor signaling (12). Moreover, previous investigations have reported immune function to be a critical factor in the development of presbycusis.…”
Section: Introductionmentioning
confidence: 95%